Nervous Systems—Composing Unruliness in the Technosphere - Maier, Stefan (Circuit)

(untitled) (Circuit, musiques contemporaines, 2022)
Proceeding from the contention that the dawn of the Anthropocene may have as much to do with our relationship to technology as it does with climate change, Stefan Maier discusses recent work that explores the unruly behaviours of particular sound technologies. As a foil to functionalist accounts of technology—accounts that attempt to understand technology entirely through the lens of normative utility—Maier discusses his idiosyncratic treatment of instruments, sound-systems and software. Here, tools are mined for their alien(ating) potential—the capacity of certain technologies to project well beyond their designated use, often to monstrous ends. In particular, Maier discusses his recent multi-media installation Deviant Chain (2019), which uses a machine-learning-driven speech-synthesizer to generate abject, nonsensical speech. These machinic glossolalia form the basis for a constructed language, which features extensively in the work.